Statistical sample in audit - Kamenska, T. O. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Audit of existing enterprises which reporting is based on large scopes of information cannot be made without use of sample survey. An auditor needs to take the decision on what set of data he/she is going to check in course of audit. Planning of a sample audit involves: selection of the data set that will be subject to sample audit; determining the number oj elements which should be selected for audit; determining a method for elements selection. When elaborating audit procedures, an auditor needs to decide about methods for selecting data for testing. An auditor can: select all the data that are subject to audit (hundred-percent audit); select specific balance sheet accounts; apply the audit to the selected accounts. When building the sample, an auditor needs to care that the general totality conforms the auditing objectives, can be applied to analysis of a certain aspect of audit, and be complete. In the auditing context, the essential meaning of categories used in statistical science are elaborated, such as risk of sample, statistical and non-statistical sample, general totality, sample elements, stratification, extrapolation, error, sample study etc. Information is given on the phases of sample audit planning, methods for selection and for determining sample size for sample audit, analysis, assessment of results and conclusions of sample audit. It is concluded that an audit won V be effectively organized and performed unless an auditor collects the sufficient amount of reliable evidences. Quantity and quality of information available with an auditor is critical for the adequacy of an auditor report. Methods and means for obtaining the auditor information should be chosen by auditors.